Maternal Folic Acid-Containing Supplement Use in Relation to Offspring Motor Function. A Prospective Study of 503 Mother-Child Dyads - Melfald Tveten, Kine; Miodini Nilsen, Roy; Dragesund, Tove (Frontiers in Pediatrics, 2022)
Background: The preventive effect of maternal folic acid use on offspring neural tube defects is well-established. However, a putative link between supplement use and other neurodevelopmental outcome is inconsistent. The aim of this study was to examine the association of folic acid-containing supplement use before and during pregnancy with motor function in children aged 3 to 18 months. Method: The study has a prospective cohort design including 503 mother-infant dyads. Motor function was measured by the Infant Motor Profile (IMP) and Ages and Stages Questionnaire Second Edition (ASQ-2). Associations between exposure and outcome were examined using linear regression analysis with robust standard error estimation. Results: Offspring total IMP score was not associated with any maternal folic acid-containing supplement use when they were used during pregnancy only (adjusted β = 0.11 95% CI = -1.19,1.40; p=0.87) or when they were used both before and during pregnancy (adjusted β = 0.22 95% CI = -0.95,1.40; p=0.70). When examining the five domain scores separately, only the IMP domain adaptability showed some association with supplement use during pregnancy (adjusted β = 2.87; 95% CI = 0.08,5.68; p=0.04), but the strength of the association was weak. Further, supplement use was not associated with any of the two motor domains of ASQ-2. Conclusion: Although no association between folic acid-containing supplement use and offspring motor function was found, the complexity of this topic and its potential mechanisms, requires further investigation. This research should include robust and accurate measures on maternal nutritional status along with thorough endpoint assessments. Keywords: Folic acid, multivitamin, motor function, medical birth registry, pediatric epidemiology, maternal health